Trade as Aid: The Political Economy of Tariff Preferences for Developing Countries - McCulloch, Rachel; Piñera, José (American Economic Review, 1977)
Trading relations have been changed during the 1970s as major industrialized countries have instituted preferential tariff schemes with developing countries in order to generate the transfer of resources. The effects of this concept, which operates as a form of assistance, have been analyzed in terms, not only of the standard customs union, but in the context of the political motives and domestic goals of the countries involved. Preferential access is examined as a potential trade-off, with emphasis on the role generalized and nonreciprocating preferences play in generating resource transfer to developing countries. The shift is seen as the result of the increasing cost of direct aid to developing countries as well as the desire of the developing countries to have more than one level of aid. 24 references. (DCK)